Evaluation of various Lichen species for monitoring pollution - lodha, abhay shantilal (Current Botany, 2013)
ABSTRACT : Lichens are small, non-vascular plants consisting of a fungus and an alga growing together in one tissue. The most commonly known lichens are those that are found on the bark of trees, or the reindeer lichens growing on the ground, but many other species grow on rocks, fences, roofs, tombstones, and other man-made objects. Even though some lichens are extremely tough and grow in very inhospitable habitats, they are also notoriously sensitive to air pollutants, primarily sulfur dioxide and heavy metals. Lichen deserts, a phenomenon where lichens disappear from cities, were described over a hundred years ago and determined to be caused by sulfur pollution. Lichens are especially sensitive to air pollutants because they have no outer impermeable layer of tissue to exclude gases and particles that impair their metabolism. Consequently, accumulation of pollutants is greater than it is in the foliage of vascular plants, which have impermeable cuticles. Lichens accumulate unusually large amounts of deposits, including heavy metals, which eventually reach toxic concentrations. Lichens are therefore excellent bioindicators and biomonitors or ecological indicators As bioindicators, the presence/absence of sensitive species is used to look for distribution patterns that reflect pollutant deposition. Voids in distributions may indicate whether lichens have died out due to heavy metals and/or sulfur oxide pollution. Lichens that do not die out, but are still present and are known to accumulate trace elements are used to indicate patterns of deposition.